2019
DOI: 10.1002/app.48021
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked PVDF‐HFP‐based hydrophobic membranes incorporated with CNF for enhanced stability and permeability in membrane distillation

Abstract: Over the past decades, numerous materials have emerged as promising amenities for the fabrication of novel membranes. The current study gives insight into a modest and effective method to fabricate a crosslinked poly‐vinylidene fluoride‐co‐hexafluoropropylene membrane with better mechanical properties and permeability for desalination. Poly‐vinylidene fluoride‐co‐hexafluoropropylene membrane was grafted with crosslinked collagen to enhance direct contact membrane distillation used for desalination. Stiffness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Remarkably, MD operations also have a higher rejection of micro-pollutants when compared with both nanofiltration (NF) and reverse osmosis (RO) processes [ 12 ]. Although MD operations can be energy-efficient and have a higher rejection percentage, membrane fouling and wetting are major concerns affecting the efficiency of the process [ 13 , 14 ]. Extensive research on the modification of polymeric membranes by the incorporation of nanoparticles (NPs) is being conducted in order to mitigate these concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, MD operations also have a higher rejection of micro-pollutants when compared with both nanofiltration (NF) and reverse osmosis (RO) processes [ 12 ]. Although MD operations can be energy-efficient and have a higher rejection percentage, membrane fouling and wetting are major concerns affecting the efficiency of the process [ 13 , 14 ]. Extensive research on the modification of polymeric membranes by the incorporation of nanoparticles (NPs) is being conducted in order to mitigate these concerns.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 3b, there are no cracks or peeling on the coating even after being immersed in water for 6 months. Such good water-proof capability originates from the hydrophobicity of P(VdF-HFP) [39] and SBR. [40] When exposed outdoors for 3 months, the coating appears the same as the pristine state without any cracks (Figure S10, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…However, they have a low piezoelectric voltage constant so that they need a high electric field for polarization, making polarization more difficult. Studies [108] were reported on the P(VDF-co-HFP) blended with other polymers such as poly(methyl methacrylate) (PMMA), PVC, poly(vinyl acetate) (PVAc) for electrolytes applications. The preparation of the composite P(VDF-co-HFP) membranes grafted by cross-linked collagen was also reported.…”
Section: Pvdf and Its Copolymer Membranesmentioning
confidence: 99%